Response Surface Methodology in Engineering Science 2021
DOI: 10.5772/intechopen.95994
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Methodology Optimization in Asphalt Mixtures: A Review

Abstract: The application of statistical modeling and optimization approaches such as response surface methodology (RSM) is important for the excellent potential to tackle different constraints and goals and the analysis of the relationships between independent factors influencing a particular response. This chapter provides a simple yet detailed literature review on the utilization of RSM for the design of experiments, modeling, and optimization of virgin and alternative materials into asphalt binder and mixtures for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…This is validated by the results obtained from the ANOVA in Table 2 which shows that based on the F-value of 23.4 and low p-values for the model as well as model terms A and B, both ZnO and TiO 2 had significant effect on the compressive strength of HPC. According to [22,27] the probability of low and F-and p-values of such magnitude being the result of noise is extremely low, at only 0.01%. Therefore, suggesting that the quadratic model presented as Equation ( 1) and developed based on the experimental values are well adequate to predict the effects of both NPs on the 28-day compressive strength of HPC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is validated by the results obtained from the ANOVA in Table 2 which shows that based on the F-value of 23.4 and low p-values for the model as well as model terms A and B, both ZnO and TiO 2 had significant effect on the compressive strength of HPC. According to [22,27] the probability of low and F-and p-values of such magnitude being the result of noise is extremely low, at only 0.01%. Therefore, suggesting that the quadratic model presented as Equation ( 1) and developed based on the experimental values are well adequate to predict the effects of both NPs on the 28-day compressive strength of HPC.…”
Section: Resultsmentioning
confidence: 99%
“…Up until now, in-stances where these substances have been implemented, the emphasis has primarily been on their individual effects, with only a limited number of attempts made to investigate the combined effects of these antimicrobial agents on the mechanical properties of concrete [19][20][21]. The use of Response Surface Methodology (RSM) provides an avenue to explore this option most especially in situations where several input variables (that is, independent variables) determines the characteristics or performance measure of a process [22,23]. The effectiveness of this approach has been demonstrated by various authors [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coe cient of determination (R 2 ) and the lack of t (LOF) are commonly presented to show the model's validity [39,40]. The LOF indicates that how much the points are not well distributed around the model, and the model cannot be used to predict the values of the dependent variable.…”
Section: Design Of Experiments Using Statistical Methodsmentioning
confidence: 99%
“…With the model F-value of 60.24 obtained from the analysis of variance (ANOVA), it can be concluded that the model is statistically significant. The probability of an F-value of this magnitude being the result of noise is extremely low, at only 0.01% [27][28][29][30].…”
Section: Modelling the Effects Of Tio2 And Zno On The Early Compressi...mentioning
confidence: 99%